SRPK2 Expression and Beta-Amyloid Accumulation Are Associated With BV2 Microglia Activation - Tian, Ziqi; Zeng, Wenfang; Yan, Cuihuan; Li, Qiang; Li, Nan; Ruan, Lin; Li, Jie; Yao, Xiaoguang; Li, Si (Frontiers in Integrative Neuroscience, 2022)
The extracellular deposition of β-amyloid (Aβ) is a pathological hallmark in Alzheimer’s disease (AD), which induces microglial activation in the pathology of AD. The expression of serine/threonine-protein kinase (SRPK2) is increased in the brain tissues of patients with AD. In this study, we examined the effect of SRPK2 in the activation of microglia. Method Microglia (BV2) cells were cultured, and the expression of SRPK2 was enhanced by transfection of SRPK2 recombinant vectors or knockdown by SRPK2 siRNA. The cells were stimulated by LPS+IFN-γ or Aβ in vitro, generating inflammatory cytokines (TNF-α, interleukin (IL) -10, IL-6) which was investigated by real-time quantitative PCR (qPCR) and ELISA. The proliferation ability of BV2 cells with/without SRPK2 expression was evaluated by WST-1 under pressure in the presence of Aβ. The effects of SRPK2 on microglia polarization were evaluated by investigating the expression of CD16/32 and CD206 by western blot, and the expression of ionized calcium binding adapter molecule 1 (IBA-1) and Arginase 1 (Arg-1) by immunofluorescence. Hippocampal cells HT-22 were cultured with a BV2 cell (with/without SRPK2 expression)-derived medium stimulated by Aβ or LPS+IFN-γ, prior to the evaluation of HT-22 cytotoxicity by assessment of cell viability. Possible relationships between Akt and SRPK2 in BV2 cells were investigated by western blot. Results The expression of SRPK2 was related to the phenotype polarization changes of microglia with increased expression of CD16/32 and IBA-1. The expression of pro-inflammatory cytokines IL-6 and TNF-α was increased, whereas the expression of anti-inflammatory cytokine IL-10 was decreased in BV2 cells with SRPK2 overexpression. Moreover, with expression enhancement of SPRK2, BV2 cells had a higher proliferation rate. Aβ treatment can promote SRPK2 expression in BV2 cell. Aβ or LPS+IFN-γ promoted the production of cytokines IL-6 and TNF-α, but decreased cytokine IL-10 in BV2 cells. SRPK2 deficiency alleviated the cytotoxic effects of Aβ or LPS+IFN-γ exposed microglia on HT22 cells. In addition, the activated Akt pathway promoted the expression of SRPK2 in BV2 cells. Conclusion Our data have found that enhanced SRPK2 expression contributed to pro-inflammatory activation of microglia. Thus SRPK2 may be a key modulating pathway of inflammatory mediators in AD pathology.